Neonatal Cerebral Sinovenous Thrombosis Post–Therapeutic Hypothermia in Perinatal Asphyxia: A Case Report - SB, Kirthana; Goyal, Medha; Mascarenhas, Dwayne; Haribalakrishna, Anitha (Journal of Pediatric Neurology, 2022)
Cerebral sinovenous thrombosis (CSVT) is an uncommon condition in neonates and often leads to adverse neurodevelopmental outcomes. A high index of suspicion for CSVT is mandated for asphyxiated infants, especially following therapeutic hypothermia (TH). Magnetic resonance venography can assist in the early detection of CSVT in suspected cases. Timely initiation of anticoagulation therapy prevents thrombus propagation and allows recanalization at around 6 to 12 weeks. Long-term follow-up is essential as cognitive impairment, motor dysfunctions, and epilepsy are common complications. Herein, we describe the clinical course of a term infant who developed CSVT in the first week of life following TH for perinatal asphyxia, its management strategies, and short-term follow-up till infancy.
Keywords: perinatal asphyxia; low/middle-income countries; complications; anticoagulation